Recent advances in the molecular prognostication of meningiomas - Wang, Elaina J.; Haddad, Alexander F.; Young, Jacob S.; Morshed, Ramin A.; Wu, Joshua P. H.; Salha, Diana M.; Butowski, Nicholas; Aghi, Manish K. (Frontiers in Oncology, 2023)
Meningiomas are the most common primary intracranial neoplasm. While traditionally viewed as benign, meningiomas are associated with significant patient morbidity, and certain meningioma subgroups display more aggressive and malignant behavior with higher rates of recurrence. Historically, the risk stratification of meningioma recurrence has been primarily associated with the World Health Organization histopathological grade and surgical extent of resection. However, a growing body of literature has highlighted the value of utilizing molecular characteristics to assess meningioma aggressiveness and recurrence risk. In this review, we discuss preclinical and clinical evidence surrounding the use of molecular classification schemes for meningioma prognostication. We also highlight how molecular data may inform meningioma treatment strategies and future directions.